Cellulose‐Based Plastic Crystal Electrolyte Membranes with Enhanced Interface for Solid‐State Lithium Batteries. Issue 7 (16th May 2021) - Zhao, Baiqing; Yang, Maoxia; Li, Jianying; Li, Shaomin; Zhang, Gen; Liu, Shiqi; Cui, Yanhua; Liu, Hao
Abstract : Fabricating robust succinonitrile‐based plastic crystal electrolyte (PCE) membranes with abundant and sustainable polymer skeleton and reinforcing the stability of the PCE–lithium anode interface are essential for adopting PCE in all‐solid‐state lithium metal batteries (ASSLMBs). Herein, renewable and low‐cost cellulose is utilized as the mechanical support framework to prepare the self‐standing cellulose‐based PCE (C‐PCE) through the facile tape‐casting method. The cellulose matrix provides excellent robustness to the hybrid C‐PCE system. The fabricated C‐PCE shows an ionic conductivity of about 2.1 × 10 −4 S cm −1 and a tensile strength of over 0.5 MPa at room temperature. Solid‐state lithium batteries assembled with the Li4 Ti5 O12 cathode, lithium metal anode, and the prepared electrolyte films exhibit an initial capacity surpassing 155 mAh g −1 at 0.2 C and room temperature. This work presents a new attempt to use low‐cost cellulose and common additives to prepare high‐performance PCE membranes for lithium‐battery applications. Abstract : Renewable cellulose is used to boost the mechanical strength of plastic crystal electrolyte (PCE), and common LiNO3 additives can effectively enhance the interface stability of PCE against Li metal anode. All‐solid‐state lithium metal batteries (ASSLMBs) assembled with a Li4 Ti5 O12 cathode and prepared cellulose‐based PCE films exhibit a long‐term cycle life at room temperature.